Mobile application design principles based on Nielsen’s and Molich’s design guidelines (NMDG) for hearing-impaired Malay Sign Language (MSL) - Ermiera Shafika, Mokhtar (2023)
This study is primarily concerned with constructing the Malay Sign Language (MSL) mobile application design principles for the hearing-impaired (HI) alpha generations based on Nielsen’s and Molich’s Design Guidelines (NMDG). Numerous MSL mobile applications have been developed and are currently available in the market to support HI learners in learning sign language interactively. Preliminary studies found that the existing MSL mobile applications fail to elicit cognitive abilities among HI learners, which is critical for improving their memorability and understanding of sign language. Previous researchers suggested hybridizing the NMDG in developing the MSL mobile applications since it could evoke cognitive ability among the users. However, the existing NMDG does not consider the context of the HI learners. Therefore, this study proposes new design principles for the MSL mobile application based on the NMDG. Two specific objectives were formulated. The Design Science Research Method (DSRM) has been adopted. Sixteen design principles were constructed through the User-Centered Design (UCD) approach. Then, the design principles were validated through three validation approaches which are expert review, prototyping, and user experience testing, to ensure it is useful and reliable. Five experts with different backgrounds were chosen to validate the design principles. Next, a semi-working prototype was successfully designed and developed based on the proposed design principles. The findings of the user experience testing indicate that the design principles can fulfil the needs of the HI alpha generations. Additionally, it can evoke cognitive ability as they can memorize and understand the application by completing the tasks within the allotted time without distractions. These findings demonstrate that the design principles can act as a manual for future researchers designing and developing the MSL mobile application for HI learners, particularly the HI alpha generations